2020
DOI: 10.1186/s12913-020-05712-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between a microfinance-based healthcare delivery platform, health insurance coverage, health screenings, and disease management in rural Western Kenya

Abstract: Background Structural barriers often prevent rural Kenyans from receiving healthcare and diagnostic testing. The Bridging Income Generation through grouP Integrated Care (BIGPIC) Family intervention facilitates microfinance groups, provides health screenings and treatment, and delivers education about health insurance coverage to address some of these barriers. This study evaluated the association between participation in BIGPIC microfinance groups and health screening/disease management outcomes. Methods Fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A study in Malawi similarly found lower out-of-pocket costs for patients in integrated care, compared to non-integrated care [63]. Intersectoral financing and/or community-based micro-financing to address both multiple determinants of health are also being explored as options to support the scale-up of integrated care [64,65]. Further, many elements of the health system put in place or strengthened for infectious disease prevention and treatment can be applied to NCD care and emerging pathogen needs, or vice versa (Table 1) [42,66].…”
Section: Integrated Service Deliverymentioning
confidence: 99%
“…A study in Malawi similarly found lower out-of-pocket costs for patients in integrated care, compared to non-integrated care [63]. Intersectoral financing and/or community-based micro-financing to address both multiple determinants of health are also being explored as options to support the scale-up of integrated care [64,65]. Further, many elements of the health system put in place or strengthened for infectious disease prevention and treatment can be applied to NCD care and emerging pathogen needs, or vice versa (Table 1) [42,66].…”
Section: Integrated Service Deliverymentioning
confidence: 99%
“…No investigators opted for the phone survey, but we received surveys from nine I-CTSI grantees and four LMIC cograntees, a response rate of 100% and 66%, respectively. As shown in table 2, 69% of survey participants stated the funding led to publications including abstracts, posters and manuscripts, with a total of 18 manuscripts published or submitted at the time of the survey 7–21. In addition, 69% of the respondents stated the funding led to further grant applications, with 38% of those applications resulting in successful funding.…”
Section: Ghri Programme Evaluationmentioning
confidence: 99%
“…As shown in table 2, 69% of survey participants stated the funding led to publications including abstracts, posters and manuscripts, with a total of 18 manuscripts published or submitted at the time of the survey. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, 69% of the respondents stated the funding led to further grant applications, with 38% of those applications resulting in successful funding. Most notably, 92% of all participants felt the funding mechanism helped All the respondents provided positive statements regarding RI potential to highlight mutual learning, building partnerships and collaborations, and shared innovation between contexts.…”
Section: Ghri Programme Evaluationmentioning
confidence: 99%
“…In recognition of the growing NCD burden in Kenya, AMPATH has established a chronic disease management program in collaboration with the Kenya Ministry of Health (MOH), operating in over 150 health facilities spanning all levels of the public sector health care system in western Kenya [ 3 ]. Over the past decade, the program has provided multicomponent care to over 40,000 individuals with hypertension and/or diabetes, grounded in the following principles: partnership with communities and governments [ 4 ], geographic decentralization of care, task redistribution [ 5 ], continuous supply of medications [ 6 ], group medical visits [ 7 ], and incorporation of social determinants of health into care delivery [ 8 ].…”
Section: Commentarymentioning
confidence: 99%